Impelementasi Sistem Parkir Otomatis Berbasis Java Desktop Menggunakan Metode Pengembangan Waterfall Pada PT. Tri Alfa Sinar Mandiri - Arizona, Nanda Diaz; Rajagukguk, Managam (Jurnal Sistem Informasi Akuntansi, 2024)
PT. Tri Alfa Sinar Mandiri is a company engaged in the field of parking system services which is a leading smart parking system provider in Indonesia by utilizing advanced technology to create an efficient, safe, and comfortable parking experience for all users. The parking system offered uses the latest technology and processes used to manage, organize, and facilitate the use of parking spaces in an efficient and structured manner. This application aims to improve comfort, security, and efficiency in finding, using, and paying for parking spaces. Some of the features include parking sensors using ultrasonic and infrared sensors to detect the presence of vehicles in each parking slot, CCTV cameras as a surveillance system to improve security in the parking area, Barrier Gate and Ticket Dispenser used as automatic access control for vehicles entering and exiting.